Decision Support System for High School Entrance Selection - Reza Zubaedah; Hertanto Prasetyo (Brilliance: Research of Artificial Intelligence, 2022)
Currently, when going to high school, a selection will be made to select students based on zoning alone. Admissions using zoning are very detrimental to students who are outside the zoning but have better grades. Schools also want to have quality students however, the existence of government regulations makes it a trick if only zoning is used as a reference. The existence of a decision support system using the SAW method helps to make alternatives by having several criteria that are used as a benchmark when making a decision. In making this decision support system can display the results of student rankings based on SAW calculations and the development method using waterfalls and making this system web-based using PHP MySQL and HTML.This research produced a decision support system that can help make it easier for schools to determine the selection of new students based on the existing zoning system and produce rankings. The results of testing accuracy increased from 56% to 100%.